Enhancing the removal of hazardous pollutants from coke making wastewater by dosing activated carbon to a pilot‐scale activated sludge process - Raper, Eleanor; Soares, Ana; Chen, J.; Sutcliffe, A.; Aries, E.; Anderson, D.; Stephenson, Tom (Wiley: 12 months, 2017)
Powdered activated carbon (PAC) was investigated for its ability to remove 6 polycyclic aromatic hydrocarbons (Σ6PAHs) (fluoranthene, benzo[b + J]fluoranthene, benzo[k]fluoranthene, benzo[a]pyrene, indeno[1,2,3-cd]pyrene, benzo[g,h,i]perylene), trace metals and colour from coke making wastewater when dosed to a pilot-plant activated sludge process (ASP). The ASP had a volume of 0.68 m3 and was operated to simulate the full-scale ASP treating coke wastewater from a steel works. Operational conditions included a flow rate of 0.78 m3/day, a hydraulic retention time of 21 hours, a sludge retention time of 38 days and a temperature of 27°C. The ASP was operated for a control period before PAC was dosed directly into the aeration cell at a dose of 400 mg/L. Powdered activated carbon addition resulted in a 20% increase in removal efficiency of the Σ6PAHs. Removal efficiency of trace metals was variable, but increased for nickel, chromium and cadmium by 22.6%, 20.5% and 12.4%, respectively. Improvement in colour removal efficiency was marginal at 5%. PAC addition allowed the improvement of treatment efficiencies in the ASP process at relatively low capital and operational costs, which may assist in reaching tighter effluent emission limits set for the industry.